2010
DOI: 10.1038/leu.2010.89
|View full text |Cite
|
Sign up to set email alerts
|

Immune recovery after fludarabine–cyclophosphamide–rituximab treatment in B-chronic lymphocytic leukemia: implication for maintenance immunotherapy

Abstract: Thirty B-cell chronic lymphocytic leukemia patients were treated with fludarabine-cyclophosphamide-rituximab (FCR) and immune cell counts (natural killer (NK) cells, CD4, CD8, Tcd and monocytes) were monitored from the end of treatment (EOT) up to 36 months (M36). Moreover, nonleukemic peripheral blood lymphocyte cytotoxicity (PBL/CTC) as well as rituximab (RTX)-dependent PBL/CTC was also measured at the initiation of therapy, EOT and M12. These parameters were correlated with post-FCR monitoring of the minima… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
40
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(41 citation statements)
references
References 23 publications
1
40
0
Order By: Relevance
“…Interestingly, MRD re-growth kinetics was predictive not only for PFS but also for OS, as described by ourselves and others ( Figures 2B and C). 17,18 Altogether, these results were very similar to those described in CLL patients treated with FCR iv formulation as front-line therapy.…”
Section: Outcomes Of Fcr In the Entire Cohortsupporting
confidence: 77%
“…Interestingly, MRD re-growth kinetics was predictive not only for PFS but also for OS, as described by ourselves and others ( Figures 2B and C). 17,18 Altogether, these results were very similar to those described in CLL patients treated with FCR iv formulation as front-line therapy.…”
Section: Outcomes Of Fcr In the Entire Cohortsupporting
confidence: 77%
“…GA101 is able to increase both direct and effector cell-mediated cytotoxicity (22) and shows higher activity than does RTX in B leukemic cell depletion (23,24). Despite a low E:T ratio in patient samples, NK cells are the main effectors of RTX-mediated ADCC of CLL cells (21,25). Moga et al (26,27) demonstrated that rhIL-15 promotes NK cell cytotoxic function from healthy donors against lymphoma cell lines or primary CLL cells.…”
mentioning
confidence: 99%
“…Despite the clear therapeutic benefits of RTX in B cell malignancies (16), relapses occur frequently following treatment. In vivo, anti-CD20 Abs induce potent target cell lysis through complement-dependent cytotoxicity (17)(18)(19) and primarily Ab-dependent cellular cytotoxicity (ADCC) (17,(19)(20)(21). ADCC relies on the ability of CD16 + effectors, such as NK cells, to bind Abs via the FcgRIIIa region.…”
mentioning
confidence: 99%
“…Prolonged CD4+ lymphopenia has been observed after fludarabine-based regimens for chronic lymphocytic leukemia. 33,34 Therefore, the use of a purine analogue (pentostatin) for the treatment of steroid-refractory GVHD may have contributed to the sustained depression of CD4+ T cells, even after all immunosuppression had been completely tapered off for almost 6 months. In Case 2, it is probable that ATG was a significant contributor to the patient's prolonged T-cell lymphopenia, a well-described phenomenon in the solid organ transplant literature.…”
Section: Discussionmentioning
confidence: 99%